2021
DOI: 10.3389/fcimb.2021.656070
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Carbapenem-Resistant Klebsiella pneumoniae in an Intensive Care Unit of a Major Teaching Hospital in Chongqing, China

Abstract: BackgroundDue to the critical condition and poor immunity of patients, the intensive care unit (ICU) has always been the main hospital source of multidrug-resistant bacteria. In recent years, with the large-scale use of antibiotics, the detection rate and mortality of carbapenem-resistant Klebsiella pneumoniae (CRKP) have gradually increased. This study explores the molecular characteristics and prevalence of CRKP isolated from the ICU ward of a tertiary hospital in China.MethodsA total of 51 non-duplicated CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 60 publications
8
17
0
Order By: Relevance
“…The detection rate of hvKP in the present study was only 1.6%, indicating that the CRKP isolates in this hospital were not yet highly virulent. This result is consistent with those of our previous study in the ICU ( Zeng et al., 2021 ). Several studies have observed that hvKP over time has been susceptible to antibiotics and related mainly to community-acquired infections ( Klaper et al., 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…The detection rate of hvKP in the present study was only 1.6%, indicating that the CRKP isolates in this hospital were not yet highly virulent. This result is consistent with those of our previous study in the ICU ( Zeng et al., 2021 ). Several studies have observed that hvKP over time has been susceptible to antibiotics and related mainly to community-acquired infections ( Klaper et al., 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“… 21 The regulator of mucoid phenotype rmpA/rmpA2, allS (involved in allantoin metabolism) and mceG (an energy-related gene) are also used to distinguish between hvKP and cKP strains. 22 , 23 A combination of these biomarkers (eg, peg-344, iroB, iucA and rmpA/rmpA2 ) showed higher accuracy in the diagnosis of hvKP than a single phenotype or single virulence-associated gene alone.…”
Section: Discussionmentioning
confidence: 99%
“…The transferability of resistance gene was determined using a conjugation experiment. As previously described ( Wang et al., 2015 ; Zeng et al., 2021 ), the conjugation test was performed by the membrane bonding method using NDM-1-producing CREL as the donor and rifampin-resistant E. coli EC600 as the recipient. Briefly, both the donor and the recipient strains were mixed on Luria-Bertani agar at a ratio of 1:2, and the mixtures were incubated at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%